2015
DOI: 10.1111/eip.12212
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism and facial emotion recognition in healthy adults

Abstract: Altered sensitivity to the emotional context represents a useful and easy way to obtain cognitive phenotype that correlates strongly with inter-individual variations in neuroticism linked to stress vulnerability and subsequent psychopathology. Present findings could have implication in early intervention strategies and staging models in psychiatry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 32 publications
2
20
2
2
Order By: Relevance
“…Based on these two results, participants with high-neuroticism showed a delay in detecting facial expressions compared to participants with low-neuroticism, although high-neuroticism participants experienced higher arousal in response to these facial expressions than did low-neuroticism participants. Our findings are in line with previous studies showing that high-neuroticism participants were less accurate in their recognition of emotional facial expressions [ 7 ], or had less gaze maintenance to the eye regions of facial expressions of others [ 8 , 9 ] compared to low-neuroticism participants. Taken together, it is suggested that people who show high levels of neuroticism avoid emotional signals in facial expressions to protect themselves from possible, but unfounded, worries [ 6 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on these two results, participants with high-neuroticism showed a delay in detecting facial expressions compared to participants with low-neuroticism, although high-neuroticism participants experienced higher arousal in response to these facial expressions than did low-neuroticism participants. Our findings are in line with previous studies showing that high-neuroticism participants were less accurate in their recognition of emotional facial expressions [ 7 ], or had less gaze maintenance to the eye regions of facial expressions of others [ 8 , 9 ] compared to low-neuroticism participants. Taken together, it is suggested that people who show high levels of neuroticism avoid emotional signals in facial expressions to protect themselves from possible, but unfounded, worries [ 6 ].…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have shown that individuals with high-neuroticism tend to avoid emotional facial expressions. For example, scores on neuroticism were negatively related to accuracy in recognizing facial emotions [ 7 ]. High-neuroticism participants looked at the eyes of emotional facial expressions for shorter durations [ 8 ] or had less gaze maintenance to the eyes of fearful faces [ 9 ] than low-neuroticism participants.…”
Section: Introductionmentioning
confidence: 99%
“…happiness, anger, fear, disgust, sadness) has also been repeatedly reported for this group of patients [27]. Moreover, the recent study conducted by our research group reported altered recognition of happy facial expression even in depression-vulnerable healthy individuals [28]. It seems that biased processing of positive emotions increases the susceptibility to negative affective states and therefore it should be a target for specific preventive strategies.…”
Section: Medicinski Podmladaksupporting
confidence: 74%
“…To our knowledge, even though there do exist some studies that have identified an association between facial emotion perception/recognition and personality traits (Andric et al, 2015;Mardaga and Iakimova, 2014), no studies to date have explored associations between these factors in BSD patients. It has been found that personality traits such as novelty seeking, harm avoidance, reward dependence and self-directedness play an important function in the development, maintenance and prognosis of BSDs (Atiye, Miettunen, and Raevuori-Helkamaa, 2015;Fassino, Amianto, Gramaglia, Facchini, and Abbate Daga, 2004).…”
Section: Introductionmentioning
confidence: 99%